Optimisation of Organisational Performance via I-Top Strategic Agility Model - Muthuveloo, Rajendran; Teoh, Ai Ping (Journal of Entrepreneurship, Business and Economics; Vol 8 No 2 (2020), 2020)
Organisational sustainability has become a major issue as organisations are struggling to achieve their targeted performance due to a dynamic business environment driven towards Industry 4.0 via technological advancement. Under such circumstances, it is a challenge for organisations to achieve the strategic agility needed for a fluid corporate strategy to manage the current disruptive business environment. To achieve optimal organisational performance, organisations must be efficient in managing time, money, and energy. The I-TOP Strategic Agility model is a very fluid model that helps organisations achieve strategic agility which is needed to manage the environmental dynamism. Optimising the return on investment (ROI) is crucial for organisational performance and sustainability. This can be achieved through the dimensions of the I-TOP Strategic Agility model called Technology Infinite Possibilities, Outright Environmental Scanning, and People-Human Capital Development. Organisations that utilise this model would be able to attain the strategic agility needed as the trendsetter and achieve business sustainability. Research paper Keywords: Organisational Performance; Strategic Agility; Technology Infinite Possibilities; Outright Environmental Scanning; Human Capital Development Reference to this paper should be made as follows: Muthuveloo, R., & Teoh, A. P. (2020). Optimisation of Organisational Performance via I-Top Strategic Agility Model, Journal of Entrepreneurship, Business and Economics , 8 (2), 154–174.